An archaeology of the cosmos : rethinking agency and religion in ancient America - Pauketat, Timothy R. (Routledge, 2013)
An Archaeology of the Cosmos seeks answers to two fundamental questions of humanity and human history. The first question concerns that which some use as a defining element of humanity: religious beliefs. Why do so many people believe in supreme beings and holy spirits? The second question concerns changes in those beliefs. What causes beliefs to change? Using archaeological evidence gathered from ancient America, especially case material from the Great Plains and the pre-Columbian American Indian city of Cahokia, Timothy Pauketat explores the logical consequences of these tw.